Decreased baroreflex sensitivity is linked to sympathovagal imbalance, low-grade inflammation, and oxidative stress in pregnancy-induced hypertension. (16th November 2016) - Subha, M.; Pal, Pravati; Pal, G. K.; Habeebullah, S.; Adithan, C.; Sridhar, M. G.
ABSTRACT: Pregnancy-induced hypertension (PIH) has been reported as a cardiovascular (CV) risk. We assessed the sympathovagal imbalance (SVI) and the association of inflammation and oxidative stress (OS) with CV risks in PIH. A total of 125 pregnant women having a risk factor for PIH were followed till term and the incidence of PIH was observed. Retrospectively, they were divided into two groups: Group I (those who did not develop PIH, n = 82) and Group II (those who developed PIH, n = 43). Blood pressure variability (BPV) parameters including baroreflex sensitivity (BRS), spectral heart rate variability (HRV), autonomic function tests (AFTs), inflammatory markers (interleukin-6, TNF-α, interferon-γ), and OS markers were measured in both the groups. Alterations in parasympathetic and sympathetic components of AFTs were analyzed. Link of various parameters to BRS was assessed by correlation and multiple regression analysis. Parasympathetic components of AFTs were decreased from the early part of pregnancy and sympathetic components were increased toward the later part of pregnancy. Decreased BRS, the marker of CV risk, was more prominent in Group II subjects. Independent contribution of interleukin-6 (β = 0.276, P = 0.020), TNF-α (β = 0.408, P = 0.002), interferon-γ (β = 0.355, P = 0.008), and thiobarbituric-acid reactive substance (β = 0.287, P = 0.015) to BRS was found to be significant. It was concluded that sympathetic overactivity that develops more in the later part (third trimester) of pregnancy contributes to SVI and genesis of PIH. In PIH women, CV risks are present from the beginning of pregnancy that intensifies in the later part of pregnancy. Retrograde inflammation and oxidative stress contribute to the decreased BRS in PIH.